Collection accessions and source material as a determining factor for producing new melon cultivars - E. A. Varivoda; Т. G. Koleboshina; М. S. Kornilova (Труды по прикладной ботанике, генетике и селекции)
Background. The main trend in melon breeding is the development of cultivars with good taste, high yield, and disease resistance. The task may be solved through a scientific search for new source material meeting these requirements.Materials and methods. The research was performed at Bykovsky Cucurbit Breeding Experiment Station. Melon accessions of various origin and F1 hybrids from the nursery of source material served as the research material. In total, during the period of 2015–2017, over 100 melon accessions were studied: 45 accessions from the VIR collection, 61 from various companies, and 12 developed at various research institutions. In the nursery of source material, the accessions were hybridized and the resulting hybrid combinations were tested, including tests against infections. All of them were evaluated for their economically useful traits, yield, taste qualities, and resistance to bio- and abiostressors. During the trials they were compared with the best released cultivars approved for dryland conditions according to the developed guidelines.Results. The purpose of this work was to study the genetic collections of melons and obtain new source forms for further breeding. As a result of the study of the collection material, 12 accessions were identified with the following economically useful traits: high yield (exceeding the reference by more than 20%), high dry matter content (from 14 to 19%), large fruit size (fruit weight higher than 4.0 kg), and other features. After hybridization and testing in F1, the following 5 hybrid combinations were distinguished: Ekler × Osen; Dyuna × Mayskaya, Sheker and No 323; Katyusha × Mestny (k-7459, Georgia); Harmony × Mestny (k7461, Georgia), characterized by a set of features important for breeding.Conclusion. Thus, for further improvement by breeding and release of new melon cultivars, source accessions were selected with a yield exceeding 15.0 t/ha, dry matter content of 13.0%, bright fruit color, and resistance to diseases.